Work Environment Challenges And Their Impact On Employee Performance In Public And Private Hospitals In The Kingdom Of Saudi Arabia (The Review of Diabetic Studies, 2025)
The work environment in healthcare institutions is a decisive determinant of employee performance, retention, and patient safety. In the Kingdom of Saudi Arabia (KSA), hospitals across public and private sectors operate under accelerating reform, rising service demand, and increasing expectations for quality, safety, and patient experience. Yet, many healthcare workers continue to report workplace challenges that undermine performance, including high workload and staffing shortages, long hours and shift-related fatigue, psychosocial stress and burnout, communication breakdowns, inconsistent leadership support, limited autonomy in clinical decision-making, and safety risks related to infection exposure, violence, and ergonomic hazards. These challenges influence clinical accuracy, timeliness of care, teamwork, and compassion, and they also shape organizational outcomes such as turnover intention, absenteeism, and patient satisfaction. This paper synthesizes the literature on work environment problems in Saudi hospitals, compares how these issues manifest in public and private settings, and outlines pathways linking workplace conditions to employee performance and healthcare quality. The paper concludes with practical, systems-level recommendations aligned with KSA’s health sector transformation goals: workforce planning and staffing optimization, fatigue risk management, supportive leadership development, psychological safety initiatives, continuous improvement in communication, and robust occupational health and safety programs. Improving the work environment should be treated as a strategic investment that simultaneously strengthens workforce well-being and elevates patient outcomes.